EFFECT OF NUTRIENT LEVELS AND SEAWEED SAP ON GROWTH AND YIELD OF BLACK GRAM (Vigna mungo L.) - HIMABINDU AMMITTE; HIKHA SINGH; HANANJAY TIWARI AND CHEREDDY MAHESHWARA REDDY (The Bioscan, 2021)
A field experiment was conducted during Kharif season 2019 at Crop Research Farm, Department of Agronomy, Sam Higginbottom University of Agriculture Technology and Sciences, Prayagraj, (U.P.) India. To evaluate the effect of Nutrient levels and Seaweed sap on growth and yield of Black gram. Foliar spray of Seaweed sap in different concentrations i.e. 2.5, 5, 7.5, 10 and 15% at 20 and 40 Days after sowing along with 100 and 75% RDF. The growth attributes which was plant height (59.42 cm), dry weight (14.68 gm plant-1), nodule count (26.44 number plant-1), number of branches (5.33 plant-1) were significantly increased with increasing concentration from 2.5 to 15%, maximum was obtained with 15% Kappaphycus alvarezii seaweed sap. Significantly highest Seed yield, net returns and benefit: cost ratio was obtained with 100% RDF + 5% K-sap (1110.31 kg/ha, 80052.62 Rs/ha, 2.38) and 75% RDF + 7.5% K-sap (1066.80 kg/ha, 75608.05 Rs/ha, 2.24). Application of 75% RDF + 7.5% K-Sap we can reduce the 25% recommended dose of fertilizers. By this we can reduce the soil pollution besides this it Produces significantly higher seed yield (26.51%) and higher net returns (34.14%) over control respectively.